Development of a rule-based system for warehouse facility layout planning - Gadam Ayyagari Lalitha (2008)
The present work focuses on developing a rule-based system for a conceptual design of a warehouse. Using the Rules Management Technology of Blaze Advisor, which is based on object oriented programming, an application is developed to estimate the gross space requirements based on the forecasts of the SKUs for a warehouse. The data component for this study is handled in the Microsoft Access database.